Meaning in Life During Covid-19 Pandemic and Social Interaction Anxiety : The Relevant Facets - Mayurakshee Gangopadhyay (Khazanah Sosial, 2021)
The meaning of life is steadily altering in the Covid-19 pandemic scenario. Since birth, life and living have been the major preoccupation of every human being. However, there remains a constant possibility of death owing to a pandemic breakout. The ways of social interaction and associated psychosocial issues are also of great importance in the present condition. This study thus aimed at finding out the interrelationship between meaning in life and social interaction anxiety among young adults. The study used a quantitative research method with the help of the Meaning in Life Questionnaire by Steger and Social Interaction Anxiety Scale by Mattick and Clarke Â on 100 samples of both the Gender, i.e., male and female aged between 21 to 25 years. The findings showed that meaning in life has a significant negative correlation with social interaction anxiety. And social interaction anxiety is found out to be negatively predicted by meaning in life.